Energy Production and Rainwater Harvesting From the Greenhouse Roof in Bashagard Region - Majid Zarezadeh; Saedeh Khwarazmi; Hoda Mansouri (آب و توسعه پایدار)
Water supply with new methods has always been emphasized by researchers and statesmen. Water scarcity and droughts in recent years in Iran have pushed the agricultural approach from traditional methods to modern methods, especially greenhouse cultivation. The advantages of this cultivation in reducing the wastage of energy and water, as well as the possibility of controlling pests and diseases, have led to an increase in the use of this method in the country. Nowadays, the use of solar panels as the roof of the structure to provide renewable energy has also been added to this process. In this research, the construction of a greenhouse structure with a roof covered with organic solar panels with south-direction and east-west orientations has been investigated by selecting a part in the Bashagard area of Hormozgan province. Modeling using PVSol software showed that the energy produced from these two types of east-west and south-direction coverage is 54293565 and 43697736-kilowatt hours per year, respectively. In addition to the aspect of energy production, based on the estimations, the roof slope was used and a piping system was created to collect rainwater in the study area, about 7500 cubic meters of rainwater was collected, which is about 4% of the amount of water consumed in this greenhouse complex.